Inflammation and thrombosis: roles of neutrophils, platelets and endothelial cells and their interactions in thrombus formation during sepsis. (21st December 2017) - Iba, T.; Levy, J. H.
Abstract : Summary: The inflammatory response and the activation of coagulation are two important responses in a host's defense against infection. These mechanisms do not work independently, but cooperate in a complex and synchronous manner. Recent research has also shed light on the critical role of thrombus formation, which prevents the dissemination of microorganisms. The cellular components of blood vessels, i.e. leukocytes, platelets, erythrocytes, and vascular endothelial cells, play significant roles in the development of thrombi in combination with activation of the coagulation system. In addition to the cellular components, alarmins such as histones and high‐mobility group box 1, microparticles and secreted granule proteins are all important for clot formation. In this summary, we review the pathophysiology of sepsis‐induced coagulopathy and the role of cellular components and critical factors released from damaged cells. In addition, we review important therapeutic approaches that have been developed, are under investigation and are currently available in certain countries, including antithrombin, recombinant thrombomodulin, anti‐Toll‐like receptor 4 therapy, anti‐damage associated molecular pattern therapy, and hemoadsorption with a polymyxin B‐immobilized fiber column.